Metabolism of the Endocannabinoid Anandamide: Open Questions after 25 Years - Maccarrone, Mauro (Frontiers in Molecular Neuroscience, 2017)
Cannabis extracts have been used for centuries, but its main active principle Δ9-tetrahydrocannabinol was identified about 50 years ago. Yet, it is only 25 years ago that the first endogenous ligand of the same receptors engaged by the cannabis agents was discovered. This “en-docannabinoid” was identified as N-arachidonoylethanolamine (or anandamide), and was shown to have several receptors, metabolic enzymes and transporters that altogether drive its biological activi-ty. Here I report on the latest advances about anandamide metabolism, with the aim of focusing open questions still awaiting an answer for a deeper understanding of anandamide activity, and for translating anandamide-based drugs into novel therapeutics for human diseases.